Utilization and optimization of unweathered and weathered basic oxygen furnace slag aggregates in cement based mortar - Omur, Tarik; Miyan, Nausad; Kabay, Nihat; Ozkan, Hakan (ELSEVIER, 2023)
The construction industry has been facing scarcity of natural aggregates due to their higher utilization in concrete and mortar. The diminution of natural resources and the increasing de-mand of natural aggregates require alternative sustainable sources. Therefore, the viability of utilizing basic oxygen furnace slag (BOFS), produced as waste during the steel manufacturing process, as fine aggregate to produce cement-based mortar has been researched in the present study. Two types of BOFS aggregates were used: (i) unweathered (collected immediately after its production) and (ii) weathered (collected after being exposed to outdoor conditions for more than 5 years) to compare their effects on mortar properties, which have not been previously reported in the literature. The experimental results indicated that the incorporation of BOFS aggregate consistently declined the flow and slightly increased water absorption and drying shrinkage. The use of 50% unweathered BOFS aggregate reduced 28-day compressive strength by only 3%, while the flexural strengths of all mortars were comparable to mortar containing 100% natural sand. The mortar mixes containing weathered BOFS aggregate exhibited comparatively lower alkali -silica expansion than that of reference, and the mortar produced with 100% weathered BOFS aggregate fulfilled the limit value of 0.1%. The experimental results and TOPSIS optimization indicated that weathered BOFS aggregate could replace natural sand up to 100% to produce mortar with reasonable strength and high-volume stability.
Keywords: Basic oxygen furnace slag aggregate; Compressive strength; Volume stability; TOPSIS; ALKALI-SILICA REACTIONS; ELECTRIC-ARC FURNACE; STEEL SLAG; FINE AGGREGATE; BOF SLAG; PERFORMANCE; CONCRETE; BEHAVIOR; POWDER; Construction & Building Technology; Engineering